Human development thresholds for inclusive mobile banking in developing countries - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2018)
This study assesses human development thresholds at which mobile banking mitigates poverty and inequality in 93 developing countries for the year 2011. Mobile banking entails: "mobile used to pay bills" and "mobile used to receive/send money", while the modifying policy indicator is the human development index (HDI). The empirical evidence is based on interactive quantile regressions. A summary of the findings shows that with increasing human development: (i) "mobiles used to pay bills" contribute to reducing inequality in countries at the bottom and top ends of the inequality distribution, while (ii) "mobiles used to receive/send money' have an appealing role in promoting inclusive development in all poverty distributions, with the exception of the top-end or 90th decile. The modifying thresholds of the HDI vary from 0.542 to 0.632 and 0.333 to 0.705 in inequality and poverty specifications, respectively. The relevance of the findings is discussed in light of the current transition from Millennium Development Goals to Sustainable Development Goals.
Keywords: G20; O40; I10; I20; I32; 330; Mobile banking; Quality of growth; poverty; inequality